Search for itineraries for the first globalization: 1519-1565 - Crespo-Francés y Valero, José Antonio (Huarte de San Juan. Geografía e Historia, 2020)
The following article, on the occasion of the 500th anniversary of the first round the world voyage of Magellan-Elcano, addresses the motivation behind the expedition, the entire scout sequence of the Pacific Ocean, together with the attempts to cross the American continent via the north, south and central area, until they settled in the Philippines and discovered the return route, thus creating the first globalmarket with the «real de a ocho» currency. The Agneses’s planisphere shows the onset of global maritime traffic, once the threatening oceans were shown to be passable. The sea routes that were established would mark the world economy for several centuries. The seas become highways connecting the pacific, Indian and Atlantic Ocean, facilitating trade and cultural exchange. Finally I present a series ofconsequences of a global nature.
Keywords: Magellan; Elcano; circumnavigation; turnaround; real de a ocho